Understanding culture, society, and politics - Alejandria-Gonzalez, Maria Carinnes P. (Makati City : Diwa Learning System Inc., 2019)
"This textbook, Diwa Senior High School Series: Understanding Culture, Society, and Politics (Second Edition), will equip you with conceptual tools from three social sciences disciplines to make sense of today's changing world. First, anthropology will provide you with its lens of cultural practices and traditions of human beings. Second, sociology will engage you in a scientific discourse of social dynamics relating to human agency. Last, political science will equip you with models and conceptual frameworks that you may use to appraise political events and behaviors".
Includes bibliography.
English text.
Keywords: Sociology; Anthropology